“We’re talking about mobility:” Discourse strategies for promoting disciplinary knowledge and language in educational contexts - Larsson, Pia Nygård (Linguistics and education, 2018)
•Explores the building of disciplinary knowledge and literacy in school contexts.•Examines teacher–student conversations as a dynamic language use.•Contributes to the understanding of content area teachers’ discourse strategies. Content area teachers have a crucial task in promoting students’ building of disciplinary knowledge and language. This paper explores, on an elaborated theoretical foundation, how subject-specific knowledge and discourse in educational contexts may be discerned and promoted. The study draws on data from an interdisciplinary design-based three-year research project. Teacher–student interaction in a lower secondary science classroom is examined, and findings from analyzed video-recorded data reveal the complex use of semiotic resources. The teacher seeks to promote student participation and raise awareness about scientific discourse. In this paper, the verbal teacher–student interaction is visualized and described, and the results display a dynamic language use, revealing how the discourse, in wavelike patterns, gradually moves towards dense nominalized expressions, aligned with the features of disciplinary discourse. The results contribute to the understanding of content area teachers’ discourse strategies when they seek to facilitate the development of disciplinary knowledge and language.